Emic Meaning of Asok Tukon and Dowry in Javanese Marriage Tradition - Nurulliza Fathimatur Rifyan (QURU’: Journal of Family Law and Culture, 2023)
In Javanese tradition, there is a custom that is practiced on the day before the marriage, namely "asok tukon". Asok tukon is a gift of a number of goods or money from the male family given to the parents of the prospective bride to the parents or family of the prospective wife. The meaning of this gift is as a form of gratitude from the male party for educating his daughter well and allowing the prospective bride to marry him. Later by the parents of the bride-to-be this asok tukon money is generally used to help with the cost of walimahan. The research type of this article is field with qualitative methods with a comparative approach. Researchers compare the meaning of asok tukon with dowry from the aspects of symbol use, values and meanings contained in these symbols. The research was conducted in Dukuh village of Salatiga City using qualitative method. The research found the types of symbols in the asok tukon tradition and their meanings emicly and looked for similarities and differences with the same symbols and meanings in the meaning of the dowry. Fundamentally, despite these differences, both Asok Tukon and dowry have symbolic value and meaning in the context of Javanese traditional marriage, and both are considered an inseparable part of the wedding procession.